Pharmacokinetics of Eight Flavonoids in Rats Assayed by UPLC-MS/MS after Oral Administration of Drynariae rhizoma Extract - Zhan-Ling Xu; Ming-Yue Xu; Hai-Tao Wang; Qing-Xuan Xu; Ming-Yang Liu; Chun-Peng Jia; Fang Geng; Ning Zhang (Journal of Analytical Methods in Chemistry)
As a traditional Chinese medicine, Drynariae rhizoma (Kunze ex Mett.) J. Sm. has been used to treat osteoporosis and bone resorption for 2500 years. Based on the previous study and literature references, flavonoids were proved to be the most abundant and main active compounds of Drynariae rhizoma for osteoporosis treatment. In order to make good and rational use of Drynariae rhizoma in future, a rapid, sensitive, and selective ultraperformance liquid chromatography-mass spectrometry (UPLC-MS/MS) method was developed to investigate the pharmacokinetics of eight main flavonoids in rat plasma after oral administration of the Drynariae rhizoma extract, including neoeriocitrin, luteolin-7-O-β-D-glucoside, astragalin, naringin, eriodictyol, luteolin, naringenin, and kaempferol. Plasma samples’ pretreatment involved a solid-phase extraction column. The separation was performed on an ACQUITY UPLCTM BEH C18 column with a gradient mobile-phase system of acetonitrile and 1% acetic acid in water. The detection was performed using a triple quadrupole tandem mass spectrometer equipped with an electrospray ionization interface (ESI) by multiple reaction monitoring (MRM) in the positive ion mode. All calibration curves exhibited good linearity (r2 > 0.9990) over the measured ranges. The intraday and interday precisions (RSD) were within 13.87%, and the accuracy (RE) ranged from −14.57% to −0.25% at three quality control levels. Extraction recovery, matrix effect, and stability were satisfactory. The pharmacokinetic characteristics of the eight flavonoids of interest were clearly elucidated.